2015
DOI: 10.3791/52359
|View full text |Cite
|
Sign up to set email alerts
|

<em>Mindfulness in Motion</em> (MIM): An Onsite Mindfulness Based Intervention (MBI) for Chronically High Stress Work Environments to Increase Resiliency and Work Engagement

Abstract: A pragmatic mindfulness intervention to benefit personnel working in chronically high-stress environments, delivered onsite during the workday, is timely and valuable to employee and employer alike. Mindfulness in Motion (MIM) is a Mindfulness Based Intervention (MBI) offered as a modified, less time intensive method (compared to Mindfulness-Based Stress Reduction), delivered onsite, during work, and intends to enable busy working adults to experience the benefits of mindfulness. It teaches mindful awareness p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
90
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 38 publications
8
90
2
4
Order By: Relevance
“…Taken together, the positive findings from the SF-36, MFIS, MHI, and FFMQ support various improvements to QOL. 15 This is important because QOL can be affected by physical, cognitive, and emotional symptoms associated with MS. 1,4,5,11,14 Mindfulness in Motion uses music and more yoga stretches than traditional mindfulness-based stress reduction, was created for working adults with limited time, and was hypothesized to be effective for people with MS. 40 Our hypothesis was confirmed in this feasibility study, which yielded significant improvements in both physical and mental health for people with MS compared with studies using mindfulness interventions that were much more time-intensive. This study has several limitations.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Taken together, the positive findings from the SF-36, MFIS, MHI, and FFMQ support various improvements to QOL. 15 This is important because QOL can be affected by physical, cognitive, and emotional symptoms associated with MS. 1,4,5,11,14 Mindfulness in Motion uses music and more yoga stretches than traditional mindfulness-based stress reduction, was created for working adults with limited time, and was hypothesized to be effective for people with MS. 40 Our hypothesis was confirmed in this feasibility study, which yielded significant improvements in both physical and mental health for people with MS compared with studies using mindfulness interventions that were much more time-intensive. This study has several limitations.…”
Section: Discussionsupporting
confidence: 64%
“…3(p 1258) The present results corroborate those of the study by Grossman et al, 8 which found statistically significant improvements in QOL and reduced depression, anxiety, and fatigue with an 8-week mindfulness-based stress reduction program (n = 74) compared with usual care (n = 74) in people with MS. Because a central piece of Mindfulness in Motion is the yoga movement, it is important to note that other interventions using yoga as the primary intervention have also found improvements in mental and physical health for people with MS. 21,22,[24][25][26][27][28][29] Mindfulness in Motion uniquely combines yoga and mindfulness, attempting to glean the benefits of both of these mind-body approaches. 40 In the present study, improvements in mindfulness were demonstrated specifically in the areas of observing, acting with awareness, nonjudgment, and nonreactivity. These findings were and psychosocial subscales and the total MFIS score; in contrast, improvement in the physical subscale was not statistically significant (Table 4).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Interventions similar to MBCT (but not MBCT specifically) have been associated with significant improvements in stress and burnout, as well as other psychological outcomes, among nurses, physicians, physical therapists, and social workers (Cohen-Katz et al 2004, 2005; Galantino et al 2005; Goodman and Schorling 2012; Klatt et al 2015; Shapiro et al 2005). Indeed, a review of ten controlled trials of Mindfulness-Based Stress Reduction (MBSR) for healthcare professionals found significant improvements in anxiety, depression, empathy, compassion, stress, burnout, spirituality, life satisfaction, rumination, and positive and negative affect after 4 to 8 weeks of mindfulness training (Irving et al 2009).…”
Section: Introductionmentioning
confidence: 99%